(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Among the thirty-eight orations by Michael Psellos collected in the first Teubner volume dedicated to him, 1 the fourth one is a ????????? ????? 2 speaking about the fasting (???????), containing also a brief reference to a situation of war and alliance with the people beyond the Danube ?? ???? ??? ?????? ????? (l. 142). 3 Since the two critic editions are full of gaps and wrong reading from the manuscript, these failings must be filled by basing upon both the studies on Byzantine scholarship developed in the last twenty years and a new careful reading of the manuscript. The text was handed down only by the Laur. 57.40 (L in Psellos traditions), 4 at. fols. 198v-202v; both the editions did not take into account manuscripts peculiarities and their apparatus are incomplete.